Transformations of Native and Added Chromium among Soil Fractions under Combined Effect of Amendments and Ageing - Neeraj Rani; Dhanwinder Singh; Nitish Dhingra (Journal of the Indian Society of Soil Science, 2024)
An experiment was carried out to study the effect of farmyard manure (FYM) and lime addition on the distribution of native and added chromium (Cr) among various soil Cr fractions, namely exchangeable and water soluble (Ex+WS), carbonate bound (CARB), easily reducible oxides (ERO’s), organic matter bound (OM), reducible oxides (RO’s), and residual (RES) fractions of non-contaminated surface soil. The study was performed with three different treatments (FYM @1%, lime @ 1% and no amendment) and for eight contact periods (1, 3, 7, 21, 42, 63, 84 and 105 days). The overall trend in Cr fractions shows that a more significant proportion of native Cr was associated with the residual fraction, followed by reducible oxide and OM fractions. The lowest concentration of Cr was observed to be in the exchangeable fraction. The addition of different concentrations of Cr increased the Cr content in each fraction with a higher increase in more labile fractions (water-soluble + exchangeable) at a lesser contact period, and further transformation of Cr to relatively lesser available fractions was observed with the increase in the time of contact. In particular, the observed variations in Cr content after a 108-day contact period compared to initial value were as follows: in Ex+WS fraction, 52.3 per cent decrease in control, 57.7 and 26.1 per cent decrease was found in FYM and lime treatments, respectively. In CARB fraction, the control showed a 17.0 per cent decrease, whereas, FYM and lime exhibited a decrease of 28.7 and 20.5 per cent, respectively. In ERO fraction, the control displayed a reduction of 41.2 per cent, while FYM and lime showed a reduction of 28.70 and 41.3 per cent, respectively. In OM fraction, the control revealed a 21.0 per cent rise, whereas, FYM and lime displayed a rise of 21.6 and 19.8 per cent, respectively. In RO fraction, the control exhibited a 52.0 per cent rise, in contrast, FYM and lime showed a rise of 60.0 and 52.4 per cent, respectively. In RES fraction, the control showed a 14.3 per cent rise, whereas, FYM and lime displayed a rise of 13.9 and 13.4 per cent, respectively.